2013
DOI: 10.3390/membranes3040331
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Gas Permeability in a Metal-Organic Framework MIL-101(Cr)–Polysulfone Mixed-Matrix Membrane with Free Volume Measurements by Positron Annihilation Lifetime Spectroscopy (PALS)

Abstract: Hydrothermally stable particles of the metal-organic framework MIL-101(Cr) were incorporated into a polysulfone (PSF) matrix to produce mixed-matrix or composite membranes with excellent dispersion of MIL-101 particles and good adhesion within the polymer matrix. Pure gas (O2, N2, CO2 and CH4) permeation tests showed a significant increase of gas permeabilities of the mixed-matrix membranes without any loss in selectivity. Positron annihilation lifetime spectroscopy (PALS) indicated that the increased gas perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 104 publications
0
38
0
Order By: Relevance
“…Examples reported by some of the present authors include storage stability predictions in epoxide mixtures, 45 characterization of nanocomposites for membrane applications, 46,47 and aging of thin polymer lms. 48,49 Recently, Chai et al used PALS to study thin lms of oleic acid-stabilized PbSe nanocrystals with respect to surface composition.…”
Section: 44mentioning
confidence: 99%
“…Examples reported by some of the present authors include storage stability predictions in epoxide mixtures, 45 characterization of nanocomposites for membrane applications, 46,47 and aging of thin polymer lms. 48,49 Recently, Chai et al used PALS to study thin lms of oleic acid-stabilized PbSe nanocrystals with respect to surface composition.…”
Section: 44mentioning
confidence: 99%
“…[69] Weight loss observed between 150 and 300 °C for MIL-101(Cr) is ascribable to residual organic linker entrapped in the inner MOF porosity. [70] The experiments carried for characterization allow to confirm the successful synthesis of MOFs.…”
Section: Resultsmentioning
confidence: 96%
“…From PALS studies, the authors concluded that the introduction of ZIF-8 in the polymer increases the free volume and the interconnectivity of the free volume of the membrane, which may result in faster diffusivities. [229]. SEM images (Figure 28a) of the MMMs showed even MOF distributions and good wetting of the particles by the polymer.…”
Section: Mofs In Mmmsmentioning
confidence: 96%